Pemberdayaan Masyarakat Melalui Pelatihan Budidaya Maggot sebagai Alternatif Pakan Ikan Lele di Desa Banyuates: (Community Empowerment Through Maggot Cultivation Training as an Alternative for Catfish Feed in Banyuates Village, Sampang Regency) - Shofiyatun Nisa'; Bagas Setyono (AL HAYAT: Jurnal Pengabdian Masyarakat, 2024)
Catfish farming is increasingly in demand by the community, but feed costs are one of the main challenges in catfish farming. The purpose of this community service is to improve the education and skills of catfish farmers in utilizing organic waste to be processed to replace processed feed utilizing organic waste to be processed into a substitute for feed in the form of maggots. Community service activities are carried out through socialization and training in maggot cultivation using organic waste as the main ingredient with the biological agent Black Soldier Fly. Maggots have a high protein content of 49.67%, carbohydrates contained in maggots of 0.18%, and fat content of 21.17%. The method used in this community service is Community Based Research, which is a community-based research that depends on the active participation of catfish farmers. This community service is carried out in several stages, namely delivering materials, questions and answers and discussions, the results of which lead to the utilization of organic waste and community education in producing maggots as catfish feed. This training is able to provide solutions and skills and increase community income from maggot cultivation for entrepreneurship.